Higiene para as escolas primárias: a produção escrita de Antonio Ferreira de Almeida Júnior (1922-1939) - Oriani, Angélica Pall [UNESP] (Faculdade de Educação da Universidade de São Paulo, 2022)
In intervention projects developed during the first decades of the 20th century in São Paulo, health and education were raised to pillars on which laid a program to regenerate society. This article includes its discussions in this scenario and discusses the knowledge of hygiene proposed for primary schools based on the written production of Antonio Ferreira de Almeida Júnior (1892-1971). Professor, physician, and education administrator, he not only defended and recommended programs aimed at teaching hygiene, but he also held positions that guaranteed him the condition of an agent that could propose and disseminate these precepts. As a chronological cutout, the years between 1922 and 1939 were considered. During this period, this professor wrote and published texts of different kind in which he addressed the importance of hygiene content in schools. Almeida Júnior’s bibliographical production was analyzed in parallel with his professional performance, which allowed us to understand his participation in medical-educational debates, which, quite punctually, defended a political project whose motto was “to clean up the population through school”. Thus, it appears that, in his writings on education, Almeida Júnior nuanced representations of childhood nature, formulated from the idea of brain plasticity, into his conceptions about the purposes of primary school and the change in teacher education based on absorbing new programs and more active teaching methods.

Nos projetos de intervenção elaborados, em São Paulo, durante as primeiras décadas do século XX, a saúde e a educação foram alçadas a pilares sobre os quais repousava um programa para regenerar a sociedade. Este artigo insere suas discussões nesse cenário e problematiza os saberes sobre higiene propostos para as escolas primárias a partir dos textos de Antonio Ferreira de Almeida Júnior (1892-1971). Professor, médico e administrador da educação, ele não somente defendeu e recomendou programas voltados para o ensino de higiene, como também ocupou cargos que lhe garantiram a condição de agente propositor e divulgador desses preceitos. Como recorte cronológico, consideram-se os anos entre 1922 e 1939, período em que o professor escreveu e publicou textos de naturezas diferentes nos quais abordou a importância dos conteúdos de higiene nas escolas. A produção bibliográfica de Almeida Júnior foi analisada em paralelo à sua atuação profissional, o que permitiu compreender a participação do professor nos debates médico-educacionais, os quais, de modo bastante pontual, defendiam um projeto político que tinha como lema “sanear a população pela escola”. Com isso, constata-se que, em seus escritos sobre educação, Almeida Júnior matizou representações da natureza infantil, formuladas a partir da ideia de plasticidade cerebral, às suas concepções acerca das finalidades da escola primária e da modificação na formação de professores a partir da incorporação de novos programas e de métodos de ensino mais ativos.
Hygiene for primary schools: the written production of Antonio Ferreira de Almeida Júnior (1922-1939)
Keywords: Primary school; Hygiene; Almeida Júnior (1892-1971); Escola primária; Higiene; Almeida Júnior (1892-1971)